2010
DOI: 10.1159/000320395
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Physical Activity, Nutrition and Lifestyle: Environmental Factors and Their Impact on IBD

Abstract: Current smoking increases the risk of developing Crohn’s disease and worsens its course, increasing the need for steroids, immunosuppressants, and re-operations. On the contrary, smoking protects against ulcerative colitis and after disease onset improves its course, decreasing the need for colectomy. Smoking cessation improves Crohn’s disease and worsens ulcerative colitis. Achieving smoking cessation in Crohn’s disease is thus an important goal of therapy, whereas patients with ulcerative colitis should not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 137 publications
1
62
1
2
Order By: Relevance
“…Evidence to date suggests that individuals with IBD should benefit from increased exercise [15,22,23,53,54], and in particular, that low-moderate intensity PA is safe [19,55]. The results from our study support these findings: no serious adverse effects related to exercise were reported.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Evidence to date suggests that individuals with IBD should benefit from increased exercise [15,22,23,53,54], and in particular, that low-moderate intensity PA is safe [19,55]. The results from our study support these findings: no serious adverse effects related to exercise were reported.…”
Section: Discussionsupporting
confidence: 85%
“…Recent evidence suggests similarities in fatigue between different conditions [12,13], though it is unclear which elements of fatigue co-exist. Although physical activity (PA) has been suggested to be appropriate for adults and children with IBD [14,15], patients may raise concerns regarding exerciserelated exacerbation of their symptoms [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking definitely is a risk factor for flares of CD and for perianal complications [78][79][80][81] . Smoking has a clear negative effect on the disease course [78][79][80][81] . On the other hand, smoking is protective and prevents flares in UC [78,82] .…”
Section: Environmental Factors Known To Play a Role For Disease Flaresmentioning
confidence: 99%
“…Smoking has a clear negative effect on the disease course [78][79][80][81] . On the other hand, smoking is protective and prevents flares in UC [78,82] . The mechanisms behind that are unclear.…”
Section: Environmental Factors Known To Play a Role For Disease Flaresmentioning
confidence: 99%
“…Increased lifetime risk to develop CD was reported in current smokers when compared with non-smokers by Calkins [53] (OR 2.0, 95% CI 1.65–2.47) as well as Mahid et al [54] (OR 1.76, 95% CI 1.40–2.22). This risk to develop CD decreases after 4 years of having quit smoking [49,55,56]. …”
Section: The Best Investigated Environmental Factor In Ibd: Smokingmentioning
confidence: 99%